2020
DOI: 10.1038/s41598-020-61693-w
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-875-5p plays critical role for mesenchymal condensation in epithelial-mesenchymal interaction during tooth development

Abstract: Epithelial-mesenchymal interaction has critical roles for organ development including teeth, during which epithelial thickening and mesenchymal condensation are initiated by precise regulation of the signaling pathway. In teeth, neural crest-derived mesenchymal cells expressed PDGF receptors migrate and become condensed toward invaginated epithelium. To identify the molecular mechanism of this interaction, we explored the specific transcriptional start sites (TSSs) of tooth organs using cap analysis of gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…In melanoma progression, PRRX1 was found upregulated and negatively correlated with miR-485-5p. 6 Wu et al found that miR-485-5p can target PRRX1 to silence its expression. As a result, inhibiting the progress of EMT.…”
Section: Prrx1 Promotes Emt Of Tumor Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…In melanoma progression, PRRX1 was found upregulated and negatively correlated with miR-485-5p. 6 Wu et al found that miR-485-5p can target PRRX1 to silence its expression. As a result, inhibiting the progress of EMT.…”
Section: Prrx1 Promotes Emt Of Tumor Cellsmentioning
confidence: 99%
“…For instance, PRRX1 can bind to the promoter region of MIR875 at −500 to +100 nts, especially the sequence of “TAATTA” at about −192 nts, which stimulates the maturation of miR-875-5p and promotes the migration of tumor cells. 6 Interestingly, Jiang et al found that PRRX1 bonded to the hypoxia response element regions of pre-miR-642b to inhibit the maturation of miR-642b-3p, which inhibited the EMT of tumor cells. 26 …”
Section: The Functional Mechanisms Of Prrx1 In Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…RNA quality was verified using an Agilent Bioanalyzer System (Agilent, Pal Alto, CA, United States), with the results revealing an RNA integrity number (RIN) >8.5 for all the samples. CAGE was performed by DNAFORM (Yokohama, Japan) as previously described (Funada et al, 2020).…”
Section: Cap Analysis Gene Expression (Cage)mentioning
confidence: 99%
“…Cldn10 may be expressed as two splice variants, Cldn10a and Cldn10b, which exhibit different expression patterns in organs. Utilizing the CAGE data, tooth-specific transcriptional start sites were explored, as previously described (Funada et al, 2020). The CAGE dataset obtained from mouse tooth germs revealed that only Cldn10b showed a high peak in tooth samples (Figure 2A).…”
Section: Cldn10b Is Highly Expressed In Developing Teethmentioning
confidence: 99%